Urgensi Layanan Bimbingan dan Konseling di Perguruan Tinggi - ulfah, ulfah (Institut Agama Islam Sumatera Barat, 2023)
College is a complex environment with students facing a variety of academic, career, and mental well-being pressures. Therefore, guidance and counseling services in higher education have increased urgency in supporting students to face these challenges. This research aims to identify the urgency of guidance and counseling services in higher education in optimizing academic development, career development and mental well-being of students. This research involves a comprehensive literature perspective on the role and benefits of guidance and counseling services in higher education. Data were analyzed by considering findings from a number of relevant studies. The research results show that guidance and counseling services in higher education have a central role in helping students achieve academic success, plan appropriate careers, and maintain their mental and emotional well-being. The urgency of this service is increasingly strengthened by changes in social dynamics, technology and an increasingly complex world of work. Therefore, investment in the development and provision of guidance and counseling services in higher education is an urgent need to support student growth and development in the modern era.